Essential mineral profiles in soils and forages in Indonesia’s active volcanoes: Implication for beef cattle nutrition in the eruption-impacted areas - Khalil, K.; Ananta, D.; Novia, R.; Suyitman, S.; Achmadi, J. (Diponegoro University, 2025)
A study was conducted to explore the essential mineral concentrations of volcanic soils and forag-es in different eruption-impacted areas and discuss the possible effects on beef cattle nutrition. A total of 75 forage and topsoil samples were collected in the eruption-impacted areas of five active volcanoes located on different islands in Indonesia: Agung Mt. (Bali), Gamalama (North Maluku), Lokon (Noth Sulawesi), Merapi (Central Java), and Sinabung (North Sumatra). The samples were analyzed for the essential macro minerals (Ca, P, Mg, K, Na, S) and trace elements (Fe, Zn, Cu, Mn, Co, Se). Results found that Ca forage varied from 0.52 to 0.76 ppm, P: 0.09-0.36%, Mg: 0.26-0.39%, K:1.55-4.21%, Na: 0.09-0.12%, and S: 0.12-0.65%. The Fe concentration of 109-308 ppm was the most varied trace element in the forages, followed by Mn (30-186 ppm, and Zn (50-85 ppm). The soils Ca, Mg, Na, and S varied from 0.38-0.87, 0.07-0.71, 0.09-0.14, and 0.01-0.07%, respectively. The potential P and Mg ranged from 48.83-174.87 and 23.99-39.97 mg/100 g, respectively. The soil was considerably rich in Fe (142,230-20,252 ppm), followed by Mn (66-180 ppm), Zn (37-56 ppm), and Cu (10-60 ppm). Con-sidering requirements for growing cattle, forage K, S, and Cu exceeded tolerable levels; they were fa-vorable to Ca, Mg, Zn, Co, and Se concentrations, but P and Na were insufficient. In conclusion, the essential minerals most likely to limit beef cattle's nutritional status and productivity in the eruption-impacted areas are K, S, Cu, P, and Na.